School Burnout as a Mediator Between Father-Love Absence and Meaning in Life Among Indonesian Adolescents - Mufied Fauziah; Dody Hartanto; Prima Suci Rohmadheny; Aprilia Setyowati; Zerlinda Aurora Saputri (Universitas Negeri Makassar, 2026)
Abstract. Adolescents face increasing family and academic demands that may compromise their psychological well-being and sense of meaning in life. Father-love absence has been identified as a significant psychological risk factor undermining adolescents' well-being, yet its mechanism in affecting meaning in life remains underexplored. This study aimed to examine the mediating role of school burnout in the relationship between father-love absence and meaning in life among vocational high school adolescents. A cross-sectional design was employed involving 290 students from three vocational high schools in Yogyakarta, Indonesia. Participants were recruited through convenience sampling, which is acknowledged as a limitation to generalizability. Father-love absence was measured using a self-developed scale based framework, school burnout was assessed using an adapted School Burnout Inventory, and meaning in life was measured using the Meaning in Life Inventory. PLS-SEM via SmartPLS was employed given the exploratory and predictive nature of the model. The results revealed that father-love absence significantly influenced school burnout, and school burnout in turn significantly and negatively influenced meaning in life. The direct effect of father-love absence on meaning in life was not significant, whereas the indirect effect through school burnout was significant, indicating full mediation. These findings suggest that school burnout serves as a critical psychological bridge through which father-love absence erodes adolescents' sense of meaning in life, highlighting the need for school-based interventions targeting burnout reduction.